Pure Beta Emitters in Water Samples from Neutron Irradiation Facilities: Activity Determination Via Vacuum Distillation and Liquid Scintillation Counting - Masci D.; Ferri D.; Gandolfo G.; Lepore L.; Contessa G.M.; Pietropaolo A.; Pillon M.; Marzo G.A. (EPJ Web of Conferences, 2023)
In the decommissioning of nuclear facilities, it is necessary to assess the radioactivity inventory for waste classification and management. For nuclear fusion experiments or accelerator-driven neutron sources, the main contribution to the radiological inventory comes from activation products and tritium. When water is used as coolant of components, it may be activated by neutrons with the consequent production of tritium, and short-lived oxygen and nitrogen isotopes. In most cases several chemical elements may be in solution or suspension in water, because of metallic pipes corrosion when occurring, or functional reasons, e.g. chemical conditioning, addition of antifreeze agent, etc. In this case other activation products could be present and need to be characterized. In this case study, a sample of the coolant of the ENEA Frascati Neutron Generator (FNG) has been radiologically, chemically and physically characterized. In such a facility, during the operation, a beam of deuterons is accelerated up to 300 keV and impacts on a tritiated target for producing 14 MeV neutrons exploiting the fusion reaction T(d,n)α. To avoid overheating in the area around the target, a water-cooling loop is used. After several years of operation, a sample of the fluid has been extracted to undergo a qualitative and quantitative analysis of the radionuclides inventory. Gamma spectrometry has not shown any presence of gamma emitters. On the other hand, Liquid Scintillation Counting (LSC) has provided evidence of the presence of beta emitters. It is known that tritium is expected to occur in the sample because of releases from the tritiated titanium target. This work concerns the development of a method to discriminate the tritium contribution with respect to the total beta activity within the FNG coolant. Since it is known that an unspecified percentage of an unknown anticorrosive agent was added to the water coolant, vacuum distillation has been used to extract purified water (containing only tritium) from the coolant sample leaving any (activated) non-volatile compound in the undistilled fraction. After distillation, any fraction has been investigated by Raman spectroscopy, to determine: a) the chemical composition of the colored anticorrosive agent, b) the efficiency of the separation. Afterwards, both fractions have been analysed by means of LSC, and results showed that the main contribution to sample activity is due to tritium and the activity values are consistent with the theoretical H atomic concentration in both fractions.